E-Commerce Untuk Usaha KonveksiZuuk Order Division - Fitriyanto, Gilang Sardika; , Nurgiyatna, S.T., M.Sc., Ph.D (2016)
Zuuk Order Division is a company engaged in the convection. For several years the ordering is still done manually, the customers come to the location and fill out the order form. To improve services especially in the ordering on the Zuuk Order Division, then apply web technology by utilizing the Internet, or called e-commerce. The website building is using the programming languages such as PHP, MySQL and the user interface is using HTML and CSS. The facilities that provided on this website such as form, gallery, map location, product information, and comments. The website was tested by conducting questionnaires to the customers. Every questionnaire was divided into two parts before and after website building. From the questionnaires showed that with website building for Zuuk Order Division further facilitate the ordering and information delivered to customers more clearly.